Analisis Keandalan Inspeksi Menara Rig dalam Operasi Pengeboran Minyak dan Gas - Satria, Frenky (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Preventing accidents during drilling and well service operations is a constant and primary concern for every company or contractor operating in the upstream business. Accident analyses often identify a number of causative factors and/or anomalies, where equipment-related items play a significant role. This article concentrates on the rig inspection process as a consistent method for detecting equipment-related anomalies before operations commence. These inspections allow necessary repairs to be made in a timely manner, thereby limiting the occurrence of accidents after the rig becomes operational. When thorough and systematic rig inspections are performed, the percentage of accidents where equipment failure is the primary cause remains very low. However, the factor of equipment condition contributing to accidents still persists in a significant number of cases. Drilling rig mast inspection is a crucial component in maintaining the safety and efficiency of drilling operations. This inspection process aims to detect structural anomalies and equipment conditions that could affect rig performance. In this study, we analyze the inspection methods applied to rig masts, including visual inspection, non-destructive testing, and condition monitoring. The results of these inspections are expected to identify potential risks and enable necessary repairs before operations begin. Through the implementation of systematic and standardized inspection procedures, companies can reduce the likelihood of accidents and equipment failures, thereby enhancing workplace safety. This study also discusses the importance of training for inspection personnel to ensure they possess the necessary knowledge and skills to detect potential problems that may arise. Thus, drilling rig mast inspection contributes not only to safety but also to overall operational efficiency.